Agomelatine or placebo as adjunctive therapy to a mood stabiliser in bipolar I depression: Randomised double-blind placebo-controlled trial. (January 2016) - Yatham, Lakshmi N.; Vieta, Eduard; Goodwin, Guy M.; Bourin, Michel; de Bodinat, Christian; Laredo, Judith; Calabrese, Joseph; ,
Abstract : Background: Adjunctive antidepressant therapy is commonly used to treat acute bipolar depression but few studies have examined this strategy. Aims: To examine the efficacy of agomelatine v. placebo as adjuncts to lithium or valproate in bipolar depression. Method: Patients who were currently depressed despite taking lithium or valproate for at least 6 weeks were randomised to treatment with agomelatine ( n = 172) or placebo ( n = 172) for 8 weeks of acute therapy and 44 weeks of continuation therapy (trial registration: ISRCTN28588282). Results: No significant differences in improvement of depressive symptoms were observed between the two groups either at 8 weeks or 52 weeks on the primary efficacy measure of change in Montgomery–Åsberg Depression Rating Scale scores from baseline to end-point. Adverse events including switches into mania/hypomania were low and similar in both groups. Conclusions: Agomelatine adjunctive therapy was not superior to placebo adjunctive therapy for acute bipolar depression.